Derivative Market Competition : OTC Versus Organized Derivative Exchanges - Nystedt, Jens (IMF Working Papers; Working Paper ;, 2004)
Recent regulatory initiatives in the United States have again raised the issue of a 'level regulatory and supervisory playing field' and the degree of competition globally between over-the-counter (OTC) derivatives and organized derivative exchange (ODE) markets. This paper models some important aspects of how an ODE market interrelates with the OTC markets. It analyzes various ways in which an ODE market can respond to competition from the OTC markets and considers whether ODE markets would actually benefit from a more level playing field. Among other factors, such as different transaction costs, different abilities to mitigate credit risk play a significant role in determining the degree of competition between the two types of markets. This implies that a potentially important service ODE markets can provide OTC market participants is to extend clearing services to them. Such services would allow the OTC markets to focus more on providing less competitive contracts/innovations and instead customize its contracts to specific investors' risk preferences and needs.